Prevention of acute ammonia toxicity in beluga, Huso huso, using natural zeolite - Farhangi, M.; Gholipour Kanani, H.; Kashani, M. (2014)
This study was accomplished to examine the efficiency of natural zeolite in preventing acute toxicity of total ammonia to Huso huso. The study was performed using Water Static Method in 96 hours. Fish averaged 46  5 g in weight and 22  4 cm in total length were exposed to four different concentrations (15, 30, 50, 75 mgL-1) of ammonia and a group was considered as control. Under stable condition, the lethal concentration of ionized ammonia was 75 mgL-1 in 96 hours. In the lethal concentration of total ammonia, different amounts of 5, 10, 15 g.L-1 granulated clinoptilolite zeolite were used. Results indicated significant differences between treatments and control (p<0.05). By increasing Clinoptilolite zeolite in each treatment, the survival rate of fish also increased significantly (p<0.05). In lethal concentration of ammonia, the use of 15 g.L-1 zeolite could prevent the mortality rate. Histopathological findings showed that major lesions in gill filaments included hemorrhage, hyperemia, hyperplasia, epithelial cells necrosis. There were hemorrhage, hyperemia, degenerated tubules of kidney, expansion of Bowman's capsule in kidney and hepatocytes necrosis in liver. Published